Effect of warm mix agent on the chemo-mechanical performance of binder with different oil sources - Chang, Rong; Sha, Aimin; Wang, Jie (Frontiers in Energy Research, 2023)
In this study, three typical oil source asphalt binders, Karamay asphalt A, CNOOC 36-1 asphalt B, Qinhuangdao CNPC asphalt C, were selected to prepare asphalt binders together with the warm mix agent Evotherm M1. The effects of warm mix agents on asphalt from different oil sources were experimentally studied via dynamic shear rheological (DSR), thermogravimetric analysis (TG), and Raman spectroscopy tests. The asphalt binders with different oil sources exhibit different properties. The rheological test results indicate that the addition of warm mix agent can delayslow down the decrease of asphalt viscosity during the aging process and delay the aging of asphalt. The results of the thermogravimetric test showed that the residual mass of asphalt with the addition of a warm mix agent significantly decreased after aging. Warm mixing agents can slow down the conversion of lightweight components to heavy components during the aging process of asphalt. By calculating the reflectivity of asphalt in Raman spectroscopy, it can be concluded that the reflectivity of asphalt decreases after adding a warm mix agentthe reflectivity of different types of warm mixed asphalt has decreased. The warm mixing agent reduces the degree of thermal evolution of asphalt. Warm mixing agents can make the chemical components in asphalt relatively stable and less prone to further pyrolysis or cracking reactions.